Do mito do feminino ao feminino do mito: o enigma da mulher nas perspectivas psicanalítica e bíblica - Souza, Ana Amália Torres (2008)
The present survey is from theorical nature and, specifically of bibliographic nature. In a interdisciplinary perspective, it intends to go deeper into the mythic dimension of female and the feminine dimension of myth, beginning from the psychoanalytic contributions of Freud and Lacan, as so the narrative analysis study of the biblical text, pointing out, in this, the study of some women in the bible (mentioned in the gospel of Mathew and participants of the Christ genealogy). Elaborated in the atmosphere of dialog between psychoanalyze and biblical literature, the present work hopes to offer contributions to the theory and psycanalitic clinic and religion science, in reference of female conception and its implications.